Genetic Variants in ERAP1 and ERAP2 Associated With Immune‐Mediated Diseases Influence Protein Expression and the Isoform Profile. Issue 2 (29th December 2017) - Hanson, Aimee L.; Cuddihy, Thomas; Haynes, Katelin; Loo, Dorothy; Morton, Craig J.; Oppermann, Udo; Leo, Paul; Thomas, Gethin P.; Lê Cao, Kim‐Anh; Kenna, Tony J.; Brown, Matthew A.
Abstract : Objective: Endoplasmic reticulum aminopeptidase 1 (ERAP‐1) and ERAP‐2, encoded on chromosome 5q15, trim endogenous peptides for HLA‐mediated presentation to the immune system. Polymorphisms in ERAP1 and/or ERAP2 are strongly associated with several immune‐mediated diseases with specific HLA backgrounds, implicating altered peptide handling and presentation as prerequisites for autoreactivity against an arthritogenic peptide. Given the thorough characterization of disease risk–associated polymorphisms that alter ERAP activity, this study aimed instead to interrogate the expression effect of chromosome 5q15 polymorphisms to determine their effect on ERAP isoform and protein expression. Methods: RNA sequencing and genotyping across chromosome 5q15 were performed to detect genetic variants in ERAP1 and ERAP2 associated with altered total gene and isoform‐specific expression. The functional implication of a putative messenger RNA splice‐altering variant on ERAP‐1 protein levels was validated using mass spectrometry. Results: Polymorphisms associated with ankylosing spondylitis (AS) significantly influenced the transcript and protein expression of ERAP‐1 and ERAP‐2. Disease risk–associated polymorphisms in and around both genes were also associated with increased gene expression. Furthermore, key risk‐associated ERAP1 variants were associated with altered transcript splicing, leading to allele‐dependent alternate expression of 2 distinct isoforms and significant differences in the type of ERAP‐1 protein produced. Conclusion: In accordance with studies demonstrating that polymorphisms that increase aminopeptidase activity predispose to immune disease, the increased risk also attributed to increased expression of ERAP1 and ERAP2 supports the notion of using aminopeptidase inhibition to treat AS and other ERAP‐associated conditions.